Nutrition in team sports - Mujika, I.; Burke, L. M. (Annals of Nutrition and Metabolism, 2010)
Team sports are based on intermittent high-intensity activity patterns, but the exact characteristics vary between and within codes, and from one game to the next. Despite the challenge of predicting exact game demands, performance in team sports is often dependent on nutritional factors. Chronic issues include achieving ideal levels of muscle mass and body fat, and supporting the nutrient needs of the training program. Acute issues, both for training and in games, include strategies that allow the player to be well fuelled and hydrated over the duration of exercise. Each player should develop a plan of consuming fluid and carbohydrate according to the needs of their activity patterns, within the breaks that are provided in their sport. In seasonal fixtures, competition varies from a weekly game in some codes to 2-3 games over a weekend road trip in others, and a tournament fixture usually involves 1-3 days between matches. Recovery between events is a major priority, involving rehydration, refuelling and repair/adaptation activities. Some sports supplements may be of value to the team athlete. Sports drinks, gels and liquid meals may be valuable in allowing nutritional goals to be met, while caffeine, creatine and buffering agents may directly enhance performance.